Sustainable Cutting Environment Evaluation for Drilling of Aluminum A380 Foam Produced by Semisolid Recycling - Igor Ćulum; Sonja Jozić; Dražen Bajić; Marijana Kalajžić (Applied Sciences)
The development of sustainable cooling technologies and increased concern for recycled materials will affect the reduction of greenhouse gas emissions, which primarily originate from the production industry. In this research paper, a twofold contribution to sustainability is made through the efficient application of a workpiece, obtained by recycling waste in the form of metal chips, and the machining of the obtained workpiece by using alternative cooling techniques comparing them to cutting fluids. Minimum quantity lubrication and cold compressed air cooling were selected as two sustainable, alternative cutting environments. Using Taguchi’s L9 orthogonal array, the influence of cutting speed, feed rate and cutting environment on drilling thrust force, built-up edge formation and hole deviation was observed. Using the analysis of variance method, feed rate was identified to have the highest influence on the output parameters (31%), followed by cooling and lubrication techniques (18%) and lastly by cutting speed (5%). Based on the grey relation analysis, optimal controllable factors were identified. This analysis indicated that low cutting speeds and feed rates, coupled with the MQL cutting environment, produced the lowest thrust force, deviation of hole and built-up edge formation.